Smart Cultivation System: Innovation Concept for Designing a Modern and Automatic Shrimp Farming Technology System Powered by Renewable Energy - Yahzunka, Adel; Budi Prasetyo , Agung; Rafiul Haq , Muhammad; Eko Firmansyah , Euaglion; Ari Prasetyo, Dafit (Ridwan Institute, 2024)
The research presents a comprehensive exploration of energy calculations and pond design for smart cultivation systems, with a focus on shrimp ponds. Through interviews and analysis, the energy consumption of various components such as lights, waterwheels, and pumps was determined, leading to the calculation of total power consumption and the specification of necessary equipment like inverters, batteries, and solar panels. Furthermore, the study proposes the integration of renewable energy sources, such as solar and wind power, into the pond system, enhancing sustainability and reducing environmental impact. The incorporation of IoT technology facilitates real-time energy monitoring and optimization. Additionally, innovative solutions like water filtration systems and solar-powered automatic feeders are introduced to improve water quality and feeding efficiency, respectively. The application of microcontroller-based solar street lighting enhances energy efficiency and maintenance ease. A SWOT analysis underscores the strengths, weaknesses, opportunities, and threats of the proposed smart cultivation system, emphasizing its potential for energy efficiency, environmental friendliness, and long-term cost savings despite challenges such as weather dependence and technological limitations. Overall, the research underscores the feasibility and benefits of integrating renewable energy and modern technology in shrimp pond management for sustainable and efficient aquaculture practices.